Optimized Microstrip Antennas with Metamaterial Superstrates Using Particle Swarm Optimization - Nooshin Feiz; Farzad Mohajeri; Anahita Ghaznavi (Bulletin of Electrical Engineering and Informatics, 2013)
Two new designs of compact microstrip antennas, where metamaterials are placed on structure as superstrate, are proposed. The newly designed metamaterial unit cell and antenna feed position optimized by particle swarm optimization. It was found that the characteristics of novel microstrip antennas with designed metamaterials placed on the superstrate are comparable to the conventional patch antennas, while their gain, directivity and radiating efficiency are noticeably improved. Gain of microstrip antenna is increased 3dB to 4dB and level of back lobe is decresed.